PENGEMBANGAN APLIKASI MANAJEMEN DATA BUKU MENGGUNAKAN APLIKASI VISUAL STUDIO CODE DENGAN FRAMEWORK LARAVEL - Adinda, Adinda Puteri Manisha; Efmi, Efmi Maiyana (Universitas Methodist Indonesia, 2025)
The management of book data in libraries or bookstores often faces challenges in terms of efficiency and data accuracy. This research aims to develop a book management application using Visual Studio Code with the Laravel framework as an effective and user-friendly digital solution. The research method used is software development research with a prototyping approach. The results of the study indicate that this application simplifies book data management, including recording, editing, and deleting data with a user-friendly and responsive interface. In conclusion, the use of Laravel in the development of book management applications provides significant benefits in enhancing the productivity of book data management.